DESAIN PEMBELAJARAN STEM PROYEK STRAW BRIDGE UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KOMPUTASIONAL SISWA SEKOLAH DASAR - Gian Tino Juniar; Dindin Abdul Muiz Lidhinillah; Srie Mulyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to develop a STEM project-based learning design using Straw Bridge to develop computational thinking skills of fifth-grade elementary school students. The method used is Educational Design Research (EDR) by McKenney & Reeves (2018), consisting of three stages: analysis and exploration, design and construction, and evaluation and reflection. The analysis and exploration stage was conducted through literature review and field study, revealing that computational thinking skills of elementary school students in Indonesia are still low, especially in algorithmic and debugging aspects. The design and construction stage produced a learning design with EDP syntax (Ask, Imagine, Plan, Create, Improve), a Student Worksheet (LKPD), and a performance assessment rubric. Validation results showed that the teaching module obtained 76% (feasible), the LKPD obtained 96.66% (very feasible), and the performance rubric obtained 78.18% (feasible). Trial implementation at SDN Gunungkoneng with 25 fifth-grade students showed that the Straw Bridge STEM learning design effectively facilitated the development of four aspects of students' computational thinking: decomposition, pattern recognition, algorithm, and debugging. The results indicate that STEM project-based learning can develop students' computational thinking skills in an authentic and meaningful context.